Pengaruh Biaya, Penempatan Kerja, Kurikulum, Metode Pembelajaran, Fasilitas dan Sertifikat Kompetensi Terhadap Keputusan Lulusan Siswa SMK Melanjutkan ke Lembaga Pelatihan - Rachman, Sinta Rosita; Nurhidayah, Nurhidayah; Basalamah, Muhammad Ridwan (LPPM Institut Pendidikan Nusantara Global, 2025)
This research aims to analyze the factors that influence the decision of Vocational High School (SMK) graduate students to continue to training institutions. This phenomenon is important considering the world of work's need for more specific and dynamic skills. This research uses a quantitative approach with logistic regression analysis techniques. It is hoped that the research results can contribute to the development of more targeted vocational education and job training policies. The results of this research found that costs, job placement, curriculum, learning methods, facilities, and competency certificates significantly influence vocational school graduates' decisions to continue their education. Competency certificates have the greatest impact, loss in validating skills. Job placement services are also important in motivating continuing education. High costs negatively influence decisions, highlighting the need for better financial support mechanisms.